Parliament and Opinion since 1832 - Cromwell, Valery (Czasopismo Prawno-Historyczne, 1989)
The role of Parliament in British Society was profoundly transformed in the nineteenth century. Society in its turn was disturbed and reconstituted by the powerful forces of accelerating industrialisation and urbanisation. Faster, easier communications and the emergence of an ever — cheaper press offered new opportunities for political activity to an ancreasingly politically sensitive nation. The key to Parliament’s survival lay in the way it was to adapt to rhese new developments. It is significant that articulate reforming groups in nineteenth-century British Society, unlike similar groups in continental Europe, had little occasion to take issue with an abstract notion like ’the state’: even rebels and radicals focussed their zeal on the reform of institutions, above all of Parliament, which retained a central place in all political discourse. In considering the complex inter-relationship between Parliament and opinion, this papier will pursue a number of very different perspectives, each of which as stimulated extensive research in the last twenty or so years. In this way it is hoped to shed some light on the ways in which Parliament was to be fundamentally transformed. Public opinion seemed to demonstrate its power over Parliament in a most dramatic way during the Reform Bill crisis of 1830 - 1832. Violent demonstrations in support of the campaign for electoral reform, an electoral reform, proved significant in the progress of events which were to ensure the final acceptance of the Bill by the House of Lords. A more „public” era for Parliament seemed to be coming into existence. Great were the hopes of the reformers and great the fears of the opponents for the future. Yet it is clear that, as a recent writer on British politics has asserted, at no point in the period 1815-1914 did Britain experience democracy. More importantly, perhaps, Britain did not and has not experienced any type of violent political revolution such as have virtually all continental European states in either the nineteenth or twentieth centuries. Some explanation of these apparently antipathetic phenomena is to be found in the functioning and responsiveness of Parliament to active external political forces.